Administrative machinery for plan implementation. IN Document Section [column] (Philippine Journal of Public Administration, 1976)
The impact of changes in the past two years has dramatically shown the resiliency of the administrative machinery to cope with the trend set by the government in accelerating the pace of socio-economic development. The period under appraisal saw far reaching changes in the administrative structure and the institutional framework for coordinated action. The first part of this overall appraisal delves on the highlights of accomplishments and developments as well as the inadequacies in the administrative machinery for plan implementation. The second part outlines several proposals or plans for future action.